A novel lightning protection technique of wind turbine components. Issue 12 (1st December 2015) - Abd‐Allah, M.A.; Said, A.; Ali, Mahmoud N.
Abstract : The lightning energy can be very harmful to wind turbine (WT) farm components; therefore an effective lightning protection technique is required. In this study, a novel technique for WT components protection is presented. This technique used ferromagnetic rings placed around the WT blade roots. Ferrite ring was moulded into particular shapes from the powder of compounds of ferric oxide, manganese, and zinc, and then sintered. The dimensions of rings used are 990 mm (inner diameter), 1030 mm (outer diameter), and 100 mm (thickness). The effectiveness of the novel technique in overvoltage mitigation during lightning strokes is presented and discussed. The results show that the overvoltage is effectively damped with using this technique. The transient overvoltage at control devices is reduced to 16% of its original value, while at distribution system; it is reduced to 5% of its original value.